The Role of Zakat in the Economy and Poverty Alleviation - Siregar, Hilyati Inayah; Chudriana Putri, Rafika; Shabri Abd. Majid, M.; Harahap, Isnaini (International Journal of Science, Technology & Management, 2023)
The main task of every government is to strive for the welfare of its entire population. According to data from the Indonesian Zakat Outlook, Indonesia has 600 networks of Zakat Management Organizations (OPZ) spread across the entire territory of the Republic of Indonesia. These networks are part of 34 National Zakat Management Bodies (BAZNAS) at the provincial level, 500 BAZNAS at the district and city levels, 24 Provincial Zakat Amil Institutions (LAZ), 14 LAZ at the provincial level, 32 LAZ at the district and city levels, and 136 Zakat Collection Units (UPZ). The research method used in this study is descriptive qualitative research, where the researcher describes the findings of the study. The research objects include relevant books and journals. The study reveals that BAZNAS and other zakat managers achieved a 1.76% poverty reduction rate in 2022.